1994
DOI: 10.1128/aem.60.10.3781-3789.1994
|View full text |Cite
|
Sign up to set email alerts
|

Ribotyping of Erwinia chrysanthemi Strains in Relation to Their Pathogenic and Geographic Distribution

Abstract: 16S and 23S rRNAs from Escherichia coli were used to study the relationship among a representative collection of strains of Erwinia chrysanthemi differing in their original host and geographical origin. Phenetic analysis of restriction fragment length polymorphisms allowed the distribution of the studied strains into seven clusters. These clusters were similar to those obtained by cladistic methods and appeared to correlate well with the established pathovars and biovars but to a lesser extent with geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
5
33
1
Order By: Relevance
“…Dickeya zeae, previously named Erwinia chrysanthemi pv. zeae, is the causal agent of maize stalk rot and rice foot rot diseases in many countries and regions (Goto, 1970;Hussain et al, 2008;Nassar et al, 1994;Samson et al, 2005;Sinha and Prasad, 1977). Outbreaks of the disease cause significant economic losses in rice and banana (Hussain et al, 2008;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dickeya zeae, previously named Erwinia chrysanthemi pv. zeae, is the causal agent of maize stalk rot and rice foot rot diseases in many countries and regions (Goto, 1970;Hussain et al, 2008;Nassar et al, 1994;Samson et al, 2005;Sinha and Prasad, 1977). Outbreaks of the disease cause significant economic losses in rice and banana (Hussain et al, 2008;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Dickeya dadantii (formerly Erwinia chrysanthemi ) strains naturally infect a large number of hosts, including food crops and ornamental plants, such as potato ( Solanum tuberosum ), chicory ( Chicorum intibus ), carrot, celery, chrysanthemum, corn, dieffenbachia and saintpaulia (Nassar et al ., 1994). During infection, the action of a set of lytic enzymes together with the resulting maceration generates large sources of nutrients for the bacteria (Hugouvieux‐Cotte‐Pattat, 2004; Kazemi‐Pour et al ., 2004; Delangle et al ., 2007; Hugouvieux‐Cotte‐Pattat and Charaoui‐Boukerzaza, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…in Denmark, England, France, Italy, the Netherlands, Romania and Greece, and includes species Dianthus barbatus and Dianthus caryophyllus (Dickey, 1979;Nassar et al, 1994;. In a study by Janse and Ruissen (1988) (Dickey, 1979;Nassar et al, 1994;Sławiak et al, 2009;Laurila et al, 2010;van der Wolf et al, 2012), Hyacinthus and sedum ( Samson and Nassan-Agha, 1978;Sławiak et al, 2009;van der Helm, 2009) (Table 2). In dahlia, Dickeya has been isolated from infected tubers (van Doorn et al, 2008).…”
Section: Host Rangementioning
confidence: 99%
“…Work in Scotland has shown that D. dianthicola is able to bind to and colonise roots of Poa annua and Solanum dulcamara under glasshouse conditions for at least 14 days (Elphinstone, 2008;Toth et al, 2011). UK (1956,1957,1958,1961,1973), Denmark (1957), Greece (1980) Denmark (1955( , 1957( ), France (1965( , 1972, UK (1956) Hellmers (1955), Nassar et al (1994) Netherlands (2009*) EFSA questionnaire 2012 New Zealand (no date) Bradbury (1986), NCPPB (online) Japan (1985) Saito (1985) Potato (Solanum tuberosum) UK (1987UK ( , 1991UK ( , 1992UK ( , 1993UK ( , 1996UK ( , 1997UK ( , 2007, Netherlands (1984( , 1986( 1987( , 1989( ), France (1975( , 1978( , 1984, Bangladesh (1988) , CFPB (online), NCPPB (online) France (1975France ( , 1978, Switzerland (1986), Brazil (no date) UK (2010), Netherlands (1983,1988,1991,1992,1993,1994), Poland, Spain, Finland (1991,1993,1903,1904,2008) Van Vaerenbergh et al (2012) Netherlands (pre-1988) Janse and Ruissen (1988) Hosts Country of isolation Reference Netherlands (1998Netherlands ( , 2001Netherlands ( , 2005…”
Section: Host Rangementioning
confidence: 99%
See 1 more Smart Citation